Understanding the Caribbean Enterprise Insights from MSMEs and Family Owned Businesses - Nicholson, Lawrence A.; Lashley, Jonathan G. (Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2016)
This engaging book fills a substantial gap in the understanding of Caribbean enterprises, focusing upon FOBs (family-owned businesses) about which, despite accounting for 70% of private sector employment in the region, very little is known. Concentrating on MSMEs which represent the majority of FOBs in the English-speaking Caribbean, the authors compare and contrast their experiences to those in developed countries, focusing in particular on areas such as family business succession, business financing and marketing. Understanding the Caribbean Enterprise provides context-specific lessons from a historical perspective of business and entrepreneurship, which in turn provide an understanding of the current issues facing MSMEs and FOBs in the English-speaking Caribbean. .